Hard challenge with soft materials: Understanding large deformation and fracture behavior - Frontini, Patricia Maria (2013)
Rubber has been recognized as an engineering material since the mid 1800s. It is well known that the mechanical behavior of rubber is complicated due to nonlinearity, hyperelasticity and its great sensitivity to the effects of temperature, environment and strain history...